A global multispecies single‐fluid MHD study of the plasma interaction around Venus. Issue 1 (31st January 2013) - Ma, Y. J.; Nagy, A. F.; Russell, C. T.; Strangeway, R. J.; Wei, H. Y.; Toth, G.
Abstract : [1] This paper reports a new global multispecies single‐fluid MHD model that was recently developed for Venus. This model is similar to the numerical model that has been successfully applied to Mars. Mass densities of proton and three important ionospheric ion species (O +, O2 +, and CO2 + ) are self‐consistently calculated in the model by including related chemical reactions and ion‐neutral collision processes. The simulation domain covers the region from 100 km altitude above the surface up to 24 RV in the tail. An adaptive spherical grid structure is constructed with radial resolution of about 5 km in the lower ionosphere. Bow shock locations are well reproduced for both solar‐maximum and solar‐minimum conditions using appropriate solar wind parameters for each case. It is shown that the shock locations are farther from the planet during the solar maximum condition, because of both the enhanced solar radiation strength and the relatively small Mach number. The simulation results also agree well with Venus Express observations, as shown by comparisons between model results with magnetic fields observed by the spacecraft. Key Points: This paper reports a new global multi‐species single‐fluid MHD model for Venus The model reproduces shock locations for both solarmax and solarmin conditions Simulation results agree well with Venus Express magnetic field observations